Pseudomyxoma Peritonei: A Case Report (Faridpur Medical College Journal, 2011)
Pseudomyxoma peritonei (PMP) is an uncommon condition characterized by abundant extracellular mucinous material in the peritoneal cavity and tumoural implants on the peritoneal and epiploic surfaces. Aim of this case report is to create awareness among the clinicians regarding this uncommon disease presented with ascites and irregular masses in the abdomen. PMP is a rare disease, may be benign or malignant, presented with ascites and irregular masses in the abdomen which is infrequently encountered in our clinical practice. Key words: Pseudomyxoma peritonei; mucinous carcinomatosis; hyperthermic chemotherapy; gelatinous material; irregular masses DOI: 10.3329/fmcj.v6i1.7415 Faridpur Med. Coll. J. 2011;6(1): 61-63